ANALISIS KETIMPANGAN PEMBANGUNAN DAN PERTUMBUHAN EKONOMI ANTAR WILAYAH KABUPATEN/KOTA DI PROVINSI SULAWESI UTARA - Gracetyani Ovicha Naibaho; Juliana Ruth Mandei; Lyndon Reinhard Jacob Pangemanan (AGRI-SOSIOEKONOMI, 2020)
This study aims to analyze the level of development inequality and economic growth between districts / cities in North Sulawesi Province in 2014-2018. This research was conducted from November 2019 to March 2020. The data used in this study are secondary data. The data were obtained from the North Sulawesi Central Statistics Agency (BPS Sulut) and other literatures according to this study. The results showed that the higher income between regions would affect economic growth and inequality that occurred in North Sulawesi Province. Based on the results of the development inequality analysis, it shows low inequality with an average Williamson Index number of 0.49 (<0.5). Classification of districts / cities in North Sulawesi Province using a regional approach. Typology Klassen is divided into four classifications. Regions are developed and growing fast, regions are developed but are depressed, regions are developing fast but are not developed, and regions are relatively underdeveloped. Based on these results, this study concludes that along with the occurrence of economic growth there will also be population growth. Thus, the rate of economic growth must exceed the rate of population growth. If in the long run the economic growth equals population growth, the regional economy will not experience development and the population's level of prosperity will not progress.